1753 Challenges in occupational health journal publishing. (24th April 2018) - Sim, MR; Guidotti, T; Härmä, M; Hobson, J; Kang, SK
Abstract : Publishing in peer reviewed scientific journals has been the traditional method to provide the research findings needed to improve occupational health practice, develop workplace exposure limits and inform policy development to better control workplace hazards. In recent years, journal publishing has faced several challenges in maintaining their influence and independence in the occupational health field. A major challenge is managing actual and perceived conflicts of interest and striking the right balance between input by industry and government in occupational health research, while preserving researcher independence. In recent years here has been a growing number of open access journals which are funded by authors paying a processing charge instead of the traditional method whereby funding comes from reader subscriptions. While there are many legitimate open access journals, this trend has given rise to what are known as 'predatory journals', which are established with the main purpose of making a profit, often having little involvement within the occupational health community and little regard for rigorous peer review. This endangers the quality of scientific publication. Another challenge for journals is how to better engage with researchers and practitioners in low and middle income countries where higher workplace hazards are more likely to occur. Content sharing to allow greater access to peer reviewed journal articles is another challenge for journals, especially as it is becoming more common for research grant bodies to require wide dissemination of the findings from studies they fund, which can conflict with journal publishing and access policies. To help editors and journals deal with the wide range of problems which can arise in the publishing process, the Committee on Publication Ethics has been established, which provides useful case studies and other resources. These issues and more will be the main focus of this workshop, with contributions by Editors from some of the main international occupational health journals.